All about breast cancer - Stephens, Fred (Oxford University P. VictoriaAU, 2001)
Presents an overview of breast cancer. Outlines categories of cancer-causing factors including: environment, smoking, hormones; and recommends preventive measures. Describes symptoms, diagnostic procedures, stages of breast cancer, approaches to treatment; and aspects of follow-up care including: complications of surgery, recurrence, and support services. Includes 8 case reports.